Hubungan Umur, Paritas, dan Tingkat Pendidikan Terhadap Penggunaan Metode Kontrasepsi Jangka Panjang (MKJP) di Rumkitban Muara Enim Tahun 2020 - Rizah Fahlevie; Helni Anggraini; Turiyani Turiyani (Universitas Batanghari Jambi, 2022)
Family Planning Program is a program that helps couples of childbearing age to avoid unwanted births, get desired births, regulate birth intervals and determine the number of children in the family through the use of contraceptives. This study aims to determine the relationship between age, perity, and level of educations on the use of long term contraceptive methods (MKJP) at Rumkitban Muara Enim in 2020. This research is a quantitative study using a cross sectional design with a sample size of 35 acceptors with a total sampling technique. Data collection was done by viewing and recording the data on Kb MKJP acceptors (IUD and Implan) in medical records, on variables of acceptors age, acceptors parity,and acceptors education level using a checklist designed by the research. This research was conducted at Rumkitban Muara Enim from July to august 2021. The data were analyzed using the fisher exact test. Based on the results of data analysis obtained at age p- value 0,004 < 0,05 with OR 10 means Ho is rejected, at parity p-value 0,033 < 0,05 with OR 5,4 means Ho is rejected and education level p-value is 0,015 < 0,05 with an OR of 7,1 means Ho is rejected. The resulst can be concluded that there is a relationship between age, parity and educations level in the use MKJP. These results can be use as a basis for information on promotif actions regarding the use of MKJP.